The impact of exchanging the light and heavy chains on the structures of bovine ultralong antibodies - Clarke, JD; Douangamath, A; Mikolajek, H; Bonnet-Di Placido, M; Ren, J; Fry, EE; Stuart, DI; Hammond, JA; Owens, RJ (International Union of Crystallography, 2024)
The third complementary‐determining regions of the heavy‐chain (CDR3H) variable regions (VH) of some cattle antibodies are highly extended, consisting of 48 or more residues. These `ultralong' CDR3Hs form β‐ribbon stalks that protrude from the surface of the antibody with a disulfide cross‐linked knob region at their apex that dominates antigen interactions over the other CDR loops. The structure of the Fab fragment of a naturally paired bovine ultralong antibody (D08), identified by single B‐cell sequencing, has been determined to 1.6 Å resolution. By swapping the D08 native light chain with that of an unrelated antigen‐unknown ultralong antibody, it is shown that interactions between the CDR3s of the variable domains potentially affect the fine positioning of the ultralong CDR3H; however, comparison with other crystallographic structures shows that crystalline packing is also a major contributor. It is concluded that, on balance, the exact positioning of ultralong CDR3H loops is most likely to be due to the constraints of crystal packing.